Motivational Effect and Importance of Subsidies and Payments for Agricultural Entrepreneurship in the Czech Republic - Katerina MAZANCOVA (Communications of International Proceedings, 2023)
Since 2004, subsidies, primarily from the European Union (EU) budget, have been a crucial source of income for rural development and agriculture in the Czech Republic. This study examines the importance and effectiveness of subsidies in farm economics through a 10-year analysis of accounting and financial statements from 12 selected farms. Guided interviews with farm representatives provide additional insights. The findings demonstrate that subsidies significantly influence farm investment decisions, with substantial amounts allocated to land, buildings, machinery, and animals. Changes in current assets depend on farming success, with a focus on increasing land ownership for protection against competing acquisitions. Foreign sources contribute to farm liabilities, while profit funds constitute the majority of own funds. Revenues from product and service sales, including subsidies, form the majority of total revenues, highlighting the increasing role of subsidies. Financial analysis reveals favorable debt ratios and liquidity levels, indicating financial independence and the ability to meet liabilities. However, subsidies can distort certain financial indicators. Despite associated administrative costs, subsidies have a positive impact on farm management. Dedicated staff members managing grant administration enable enterprises to optimize their grant potential for further investments. The study also highlights challenges related to crop yield predictability, livestock risks, and fluctuating purchase prices of agricultural commodities. These findings underscore the importance of subsidies for farm economics and offer insights into their effectiveness. The research contributes to ongoing discussions on subsidy impacts and informs future agricultural policies and subsidy schemes in the Czech Republic and the European Union.
Keywords: agriculture; subsidies; Czech Republic